Coincidence point theorems for geraghty-type contraction mappings in generalized metric spaces - Atit Wiriyapongsanon (2018)
© 2018 by the Mathematical Association of Thailand. All rights reserved. In 2005, Jleli and Samet introduced a new concept ofs generalized metric spaces which cover standard metric spaces, b-metric spaces and dislocated metric spaces. In this paper, we prove some coincidence theorems for Geraghty-type contraction mappings in partially ordered generalized metric spaces. Moreover, we obtain a coupled coincidence point result as a corollary of our main theorem. Finally, we give an example to support our results.